2005
DOI: 10.1152/ajpgi.00208.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transmural gradient of leukocyte-endothelial interaction in the rat gastrointestinal tract

Abstract: -Gastrointestinal injury usually starts in the superficial mucosa. We investigated whether leukocyteendothelial interactions were greater in the gastrointestinal mucosa than the submucosa and muscularis in control tissue and after upregulation of adhesion molecules with endotoxin and after chemical insult with nonsteroidal anti-inflammatory drugs. Inactin-anesthetized rats were given either endotoxin, flurbiprofen, or nitric oxide (NO)-flurbiprofen, after which ICAM-1 and P-selectin expression was measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…These results do, however, agree with earlier studies from our laboratory showing that the superficial gastric and duodenal mucosal microcirculation have much lower density of intercellular adhesion molecule-1 and P-selectin and also less leukocyteendothelial interactions than occur in the deeper layers of the gut wall (39). This was true even during stimulated upregulation with endotoxin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results do, however, agree with earlier studies from our laboratory showing that the superficial gastric and duodenal mucosal microcirculation have much lower density of intercellular adhesion molecule-1 and P-selectin and also less leukocyteendothelial interactions than occur in the deeper layers of the gut wall (39). This was true even during stimulated upregulation with endotoxin.…”
Section: Discussionsupporting
confidence: 92%
“…Values were obtained for leukocyte adhesion and rolling as previously described (39). Leukocytes were regarded as adherent if they remained stationary for 30 s and longer and rolling if they moved with a lower velocity than red blood cells.…”
Section: P-selectin Antibody Experiments: Experimental Design (Group I)mentioning
confidence: 99%
“…Mangell et al investigated the role of P-selectin-dependent leukocyte recruitment in LPS-induced intestinal barrier dysfunction in mice [40]. This study is particularly important as it showed that LPS-induced leukocyte recruitment is mediated by P-selectin.…”
Section: Resultsmentioning
confidence: 99%